Notes on late Cenomanian and Turonianammonites from Touraine, Western France - Kennedy, W; Amédro, F; Badillet, G; Hancock, J; Wright, C (1984)
Recent collecting in the type area of the Turonian stage and adjacent parts of Touraine in western France provides new geographic and stratigraphic records as well as additional systematic information on species of the ammonite genera Puzosia, Watinoceras, Metoicoceras, Mammites, Prohauericeras, Collignoniceras, Lecointriceras, Subprionocyclus and Sciponoceras. © 1984 Academic Press Inc. (London) Ltd.